FACTORS INFLUENCING JOB SATISFACTION: A STUDY OF EMPLOYEE ENVIRONMENT, MOTIVATION, AND DISCIPLINE - Maulidina, Annisa; Sariwulan, Tuty; Faslah, Roni (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to determine the effect of work environment, work motivation and work discipline on job satisfaction at PT Meindo Elang Indah. The research method used in this study is a quantitative method with primary data through the distribution of questionnaires. The population in this study was 180 employees. The technique in determining the sample in this study used the proportional random sampling technique with an error rate of 5% so that the sample in this study amounted to 124 employees. The results of the analysis using Partial Least Square (PLS) show that the work environment variable has a significant effect on work discipline, work motivation has a significant effect on work discipline, the work environment has a significant effect on job satisfaction, work motivation has a significant effect on job satisfaction, work discipline has a significant effect on job satisfaction, the work environment has a significant effect on job satisfaction through work discipline, and work motivation has a significant effect on job satisfaction through work discipline.